Groundwater Quality Assessment and Potential Public Health Risks in Rural Agricultural Areas of Indonesia: A Physicochemical and Microbiological Approach - Rio Rinaldy; Siti Hapsah Pahira (Syntax Corporation Indonesia, 2026)
Groundwater is a critical water source for rural communities, particularly in areas where centralized water-supply systems are limited or absent. Despite its essential role, groundwater quality in agricultural regions of Indonesia remains insufficiently monitored, creating a significant gap in public health surveillance and environmental management. Previous studies have assessed groundwater quality in urban or peri-urban contexts; however, integrated physicochemical, microbiological, and spatial assessments in rural agricultural settings of West Java Province remain scarce. This study aimed to assess the physicochemical and microbiological quality of groundwater in a rural agricultural area in Indramayu District, West Java Province, Indonesia, and to identify potential contamination risks associated with land use and local environmental conditions. A total of 30 household well samples were collected and analyzed for pH, temperature, total dissolved solids (TDS), electrical conductivity, dissolved oxygen, salinity, nitrate, phosphate, iron, manganese, and total coliform. Spatial distribution of contamination risk was assessed through ArcGIS-based distribution mapping. The results showed that most basic physicochemical parameters were generally within acceptable ranges. Nevertheless, several wells showed elevated TDS, nitrate, iron, and total coliform levels. Nitrate concentrations ranged from 2.40 to 62.50 mg/L, with sampling points S8, S9, S10, and S18 exceeding the WHO guideline value of 50 mg/L. Microbiological contamination was a major concern, as only 8 of 30 samples (26.67%) met the safety requirement of 0 MPN/100 mL for total coliform. Spatial analysis indicated that high-risk wells were concentrated near agricultural land, residential settlements, and drainage channels, reflecting the combined influence of fertilizer application, septic tank leakage, domestic wastewater, and surface runoff infiltration. These findings confirm that rural groundwater quality in Indramayu District is compromised by both agricultural and domestic pollution sources, with direct implications for waterborne disease risk and long-term public health. Integrated monitoring, improved well construction standards, adequate septic tank setback distances, sanitation system improvements, and community-level water treatment are urgently recommended.